The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13143445
|View full text |Cite
|
Sign up to set email alerts
|

Akt Isoforms: A Family Affair in Breast Cancer

Abstract: Akt, also known as protein kinase B (PKB), belongs to the AGC family of protein kinases. It acts downstream of the phosphatidylinositol 3-kinase (PI3K) and regulates diverse cellular processes, including cell proliferation, cell survival, metabolism, tumor growth and metastasis. The PI3K/Akt signaling pathway is frequently deregulated in breast cancer and plays an important role in the development and progression of breast cancer. There are three closely related members in the Akt family, namely Akt1(PKBα), Ak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 169 publications
0
18
0
Order By: Relevance
“…Akt is hyperactivated in most breast cancers and, in recent years, several inhibitors that block the phosphorylation of the enzyme have been identified, despite the high homology among the Akt isozymes which made it difficult to develop isoform-specific drugs [ 33 ]. In breast tumors as in other cancers, growing evidence shows distinct and perhaps opposite oncogenic functions of Akt isozymes, the expression of which may also vary in primary and secondary sites of tumors [ 11 , 15 ]. Based on the need of precise isoform-specific inhibitors, especially in the treatment of the most aggressive breast cancers, the role of Vav1 as a potential down-regulator of individual Akt isozymes was investigated in the MDA-MB-231 cell line, highly invasive and with a triple negative phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akt is hyperactivated in most breast cancers and, in recent years, several inhibitors that block the phosphorylation of the enzyme have been identified, despite the high homology among the Akt isozymes which made it difficult to develop isoform-specific drugs [ 33 ]. In breast tumors as in other cancers, growing evidence shows distinct and perhaps opposite oncogenic functions of Akt isozymes, the expression of which may also vary in primary and secondary sites of tumors [ 11 , 15 ]. Based on the need of precise isoform-specific inhibitors, especially in the treatment of the most aggressive breast cancers, the role of Vav1 as a potential down-regulator of individual Akt isozymes was investigated in the MDA-MB-231 cell line, highly invasive and with a triple negative phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivation of Akt signaling is a central event in human cancer and almost 30% of TNBCs have alterations in the PI3K/Akt/mTOR pathway [ 7 , 8 ]. The Akt family includes three members (Akt1, Akt2 and Akt3) that play distinct roles in breast cancer malignancy, being Akt1 correlated with proliferation of tumor cells and the other two isozymes variously involved in invasion/metastasis [ 9 , 10 , 11 ]. In tumors with a triple negative phenotype, Akt2 has a crucial role in metastasis by regulating the epithelial-to-mesenchymal-transition (EMT) and by enabling extravasation through the vessel wall [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drago-Ferrante and colleagues demonstrated that miR-29b1-5p expression is strongly down-regulated in TNBC tissues and cell lines and this impacts on proliferation and migration of TNBC-derived cells [ 24 ]. They found that the over-expression of miR-29b1-5p in MDA-MB-231 cells decreases in vitro growth rate, Ki-67 levels, and migration [ 24 ], and the decrease of Wnt/βcatenin and Akt-signaling pathways, both involved in tumorigenesis and progression of breast cancer [ 74 , 75 ]. In addition, it was demonstrated that miR-29b1-5p down-modulates, at both mRNA and protein levels, spindlin 1 (SPIN1), which enables methylated histone binding activity and participates in PI3K/Akt-mediated chemoresistance of metastatic breast cancer [ 24 , 76 ].…”
Section: Roles Of Mir-29b In Breast Cancermentioning
confidence: 99%
“…AKT isoforms can specifically regulate several cellular processes. While all isoforms seem to downregulate autophagy, AKT1 and AKT3 seem to be involved in cell proliferation and AKT1 and AKT2 in the regulation of the cancer cell metabolism [ 13 ].…”
Section: Introductionmentioning
confidence: 99%